Deficit of conceivability: response to Bogdan Faul’s article «Minimal dualism and epistemic approach» - T. S. Demin (Омский научный вестник: Серия "Общество. История. Современность")
The argument in defense of minimal dualism presented in Bogdan Faul’s article presents the idea that we can conceive consciousness existing only in the introspection without a physical body. From that kind of conceivability follows the possibility of consciousness. And this leads to the falsity of physicalism. I argue that Faul’s argument is not fundamentally different from the ghost argument. Then I consider a step from conceivability to possibility and conclude that no argument of conceivability guarantees the possibility that consciousness is non-physical since we lack the epistemic capacity for such a conclusion. In the last part of this article, I discuss three kinds of conceivability. The classification of these kinds of conceivability demonstrates what kind of conceivability we lack for an argument to be sound, and we cannot have such conceivability